Studi Eksperimental Pengaruh Waktu Pemaparan Asap Obat Anti Nyamuk Bakar pada Perubahan Histopatologi Ginjal Tikus Jantan Wistar - Eva Vidella; Mulyati Sri Rahayu; Khairunnisa Khairunnisa (Pusat riset dan Inovasi Nasional, 2025)
Mosquito coil smoke is the most commonly used insecticide by the public for mosquito control. The main active ingredient in these products is a pyrethroid derivative called Allethrin, which can generate free radicals that potentially damage the kidneys. This study aimed to evaluate the effect of varying durations of exposure to mosquito coil smoke on the histopathological features of the kidneys in male Wistar rats (Rattus norvegicus). The research employed a laboratory experimental method with a Post-Test Only Group Design. A total of 24 male Wistar rats were divided into four groups: a control group without treatment and three treatment groups exposed to mosquito coil smoke for 5 hours, 7 hours, and 9 hours per day over 21 days. After the treatment period, the rats were euthanized by cervical dislocation, their kidneys were harvested, and histopathological preparations were made and scored using the Venient et al. scoring system. Statistical analysis using the Kruskal-Wallis and Mann-Whitney tests revealed significant differences in kidney damage between the control and treatment groups (p < 0.001). The study concluded that varying durations of exposure to mosquito coil smoke cause significant differences in kidney histopathological damage in rats, with the most severe damage observed in the group exposed for 9 hours per day.